2006
DOI: 10.1097/01.prs.0000214656.07273.b0
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Two Novel Dermal Fillers: Histological Evaluation of Implants of a Hyaluronic Acid Filler and a Polyacrylamide Filler

Abstract: This study reveals that two soft-tissue fillers considered to be biocompatible induce very different tissue reactions. This indicates that their behavior in clinical practice is likely to be different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 18 publications
1
41
0
3
Order By: Relevance
“…Cross-linked hyaluronic acid (HA) derivatives are non-permanent dermal fillers used not only for the correction of HIV-LA, but also for treatment of photodamaged skin [13], facial atrophic scars [14] and other cosmetic purposes [15,16,17]. Histologic analyses of the forearm, buttock and iliac crest skin injected with different types of cross-linked HA have shown that HA implants have the ability to bind water and thereby provide volume and support to the injected tissue for up to 12 months without causing fibrosis or foreign body reactions [18,19,20,21]. Recent studies suggest that these fillers may stimulate dermal collagen anabolism by inducing increased procollagen and tissue inhibitor of matrix-degrading metalloproteinases (TIMP-1) levels [13,22].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linked hyaluronic acid (HA) derivatives are non-permanent dermal fillers used not only for the correction of HIV-LA, but also for treatment of photodamaged skin [13], facial atrophic scars [14] and other cosmetic purposes [15,16,17]. Histologic analyses of the forearm, buttock and iliac crest skin injected with different types of cross-linked HA have shown that HA implants have the ability to bind water and thereby provide volume and support to the injected tissue for up to 12 months without causing fibrosis or foreign body reactions [18,19,20,21]. Recent studies suggest that these fillers may stimulate dermal collagen anabolism by inducing increased procollagen and tissue inhibitor of matrix-degrading metalloproteinases (TIMP-1) levels [13,22].…”
Section: Introductionmentioning
confidence: 99%
“…After injection, a fibrocellular capsule is formed. After 6-9 months the gel is dispersed into the skin and is surrounded by macrophages and fibroblasts 7,8 . Injected in medium or larger quantities, as for breast augmentation, a cellular foreign body reaction may occur 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Es wird beim Menschen seit einigen Jahren zur Unterstützung von subkutanem Gewebe, sowie zur Therapie der stressbedingten Inkontinenz der Frau eingesetzt (Lose et al 2006, Pallua und Wolters 2010. Humanmedizinische Studien zeigen eine gute Gewebeverträglichkeit und einen lang anhaltenden Effekt, da die Substanz in das Weichteilgewebe integriert werden soll (Fer-nández-Cossio und Castano-Oreja 2006, Christensen et al 2003, Christensen et al 2008, Bello et al 2007 …”
Section: Polyacrylamid Hydrogelunclassified